Relationship between Innovation Climate, Market Orientation and corporate entrepreneurship - Abdallah Ahmed, Nazar Omer (International Review of Management and Marketing, 2016)
A great deal of the literature on corporate entrepreneurship assumes that it is important and desirable to foster corporate entrepreneurial thinking and behavior in organizations. While much has been written about the need for established firms to become entrepreneurial, not much progress has been made to determine exactly how entrepreneurship can be accomplished and sustained in these organizations. The purpose of this study is to investigate the relationship between market orientation, innovation climate and corporate entrepreneurship. Self-administrated questionnaires were used for data collection from the population representatives by means of convenience sampling. 165 questionnaires were received back out of 200.Regressin analysis were used to analyze the relationship between the variable of study. Results showed a positive relationship between market orientation, innovation climate and Intrapreneurship Keywords: Innovation Climate; Market Orientation; corporate entrepreneurship; Entrepreneurship. JEL Classifications: L2, L26